ALTERNATIVE SOLUTIONS TO PSYCHOLOGICAL PROBLEMS OF ADOLESCENT PERIOD - D. M. Shokirov (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the concept of alternative solutions to the psychological problems of adolescence in order to implement the idea of developing the mature generation.